Mixed neuropathologies and estimated rates of clinical progression in a large autopsy sample. Issue 6 (18th November 2016) - Brenowitz, Willa D.; Hubbard, Rebecca A.; Keene, C. Dirk; Hawes, Stephen E.; Longstreth, W.T.; Woltjer, Randy L.; Kukull, Walter A.
Abstract: Introduction: Whether co‐occurring neuropathologies interact or independently affect clinical disease progression is uncertain. We estimated rates of clinical progression and tested whether associations between clinical progression and Alzheimer's disease neuropathology (ADNP) were modified by co‐occurring Lewy body disease (LBD) or vascular brain injury (VBI). Methods: Linear mixed effects models evaluated longitudinal trends in the Clinical Dementia Rating Scale Sum of Boxes on 2046 autopsied participants seen at a U.S. Alzheimer's Disease Center. Results: Annual clinical progression was slightly faster for ADNP + LBD compared with ADNP only ( P  = .06) and slightly slower for ADNP + VBI ( P  = .003). Differences in progression were less than expected if each neuropathology independently contributed to progression; ADNP interacted with LBD ( P  = .002) and VBI ( P  = .003). In secondary models, the effect of additional pathologies on clinical progression was greater in those with intermediate compared with high levels of ADNP. Discussion: The impact of co‐occurring pathologies on progression may depend on severity of ADNP.